Essential Oils from Ocotea Species: Chemical Variety, Biological Activities and Geographic Availability - Echeverria-Morgado, J (Elsevier B.V., 2022)
This review describes the chemical composition and biological properties of essential oils from plants of the Ocotea genus, from different origin. This taxon belongs to the Laureaceae family, which in turn, is best known for medicinal use, often related to the essential oils. The text includes studies about Ocotea species distributed mainly on the South American continent, but also reporting species located in North America and Africa. Brazil, Colombia, Costa Rica and Ecuador are countries with highest number of species mentioned in the review. Also, the major components of each essential oil, its chemical structures, as well as the description and extent of biological activities related to essential oils are detailed in this review. Finally, the text discusses the chemical and biological aspects of these studies in a comparatively way, also informing additional data such as yield, biome of origin and pharmacobotanical location. © 2021 Elsevier B.V.